Dopamine dysregulation syndrome after prescription of dopamine agonists: a case report - M.L. Costa; A. Cerame (European Psychiatry, 2022)
Introduction We present the case of a 65-year-old woman with multiple and chronic psychosomatic symptoms. Due to motor impairments she was diagnosed in 2009 with Parkinson’s Disease (PD) by the neurology department and empirical treatment with levodopa was prescribed. However, the patient increased her levodopa intake by three times the recommended dose. The patient presented many adverse effects, including psychotic symptoms, that were interrupted after the levodopa intake was ended during a two month internament in a psychiatric unit. Dopamine dysregulation syndrome (DDS) is a condition in which patients with PD increase their levodopa intake without an objective worsening of motor symptoms. Higher-than-prescribed doses are taken by patients who develop tolerance and dependence to dopaminergic agonists.